ZAKAH EMPOWERMENT OPTIMIZATION THROUGH BAITUL IKHTIAR COOPERATION AS AN EFFORT IN POVERTY ALLEVIATION IN BOGOR REGENCY - Hamzah Hamzah (Universitas Islam Negeri Jakarta, 2018)
The Indonesian government and other concerned parties have conducted various programs looking for strategies for poverty alleviation, however, the poverty rate has not decreased significantly. One of zakah based empowerment paradigm is transformation paradigm that is a process in motivating the society with new values which can enlighten the soul, spirit and the common sense, so that they can rediscover their way of life from being a mustahiq (a person who receives zakah) to muzakki (person who gives zakah). This empowerment was an important development pillar in stimulating development growth and equality, providing the societies’ welfare, creating jobs opportunity and alleviating poverty. The research is conducted by surveying the respondents in three sub districts in Bogor Region. The respondents are 254 mustahik that consists of 66 mustahik vegetables producers in Cibungbulang sub district, 85 mustahik as sate skewers producers in Tenjolaya sub district and 103 mustahik as shoes-sandals producers in Taman Sari sub district. The field research was conducted in 2013. The research instrument/questionnaire was based on the concept of empowerment and independence. The method used in the research was descriptive statistic and T-test.